2019
DOI: 10.1002/jmri.26651
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of radiotherapy‐induced cerebral microbleeds and serial analysis of their size compared with white matter changes: A 7T MRI study in 113 adult patients with brain tumors

Abstract: Background Although radiation therapy (RT) contributes to survival benefit in many brain tumor patients, it has also been associated with long‐term brain injury. Cerebral microbleeds (CMBs) represent an important manifestation of radiation‐related injury. Purpose To characterize the change in size and number of CMBs over time and to evaluate their relationship to white matter structural integrity as measured using diffusion MRI indices. Study Type Longitudinal, retrospective, human cohort. Population In all, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Morrison et al, however, found no association between maximum radiation dose to the brain and microbleed development in adult brain tumor patients 15 . Similarly, in a previous study of 90 children treated with cranial radiation for a mixture of CNS tumors and leukemias, no significant difference in cerebrovascular abnormalities were found between patients treated with low (18 Gy) or high (at least 32 Gy) doses of CRT 4 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Morrison et al, however, found no association between maximum radiation dose to the brain and microbleed development in adult brain tumor patients 15 . Similarly, in a previous study of 90 children treated with cranial radiation for a mixture of CNS tumors and leukemias, no significant difference in cerebrovascular abnormalities were found between patients treated with low (18 Gy) or high (at least 32 Gy) doses of CRT 4 .…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our study, Neu et al, using SWI on a 3 T MRI platform, found that 36 of 40 (90%) of brain tumor survivors treated with cranial radiation had microbleeds at a mean of 13.5 years after diagnosis 14 and the total number of microbleeds correlated with greater whole brain radiation dose and time since diagnosis. A recent study of 113 adult brain tumor patients treated with cranial radiation who received serial SWI's at 7 T were found to have an 18% increase in volume and 11% increase in number of microbleeds per year 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study deploying T2*-weighted and SWI sequences (1,5T or 3T), the prevalence was as high as 90% after a mean observational period of 13,5 years [52]. Using 7T MRI this number is much higher with CMBs being found in up to 100% of patients [53]. CMBs might be detected as soon as 3-4 months after radiotherapy onset, with a latency of up to 9 years (mean 33 months) [54], therefore representing both early-delayed and late-delayed injury.…”
Section: Cerebral Microbleedsmentioning
confidence: 97%
“…Another study of 7T SWI in 113 patients having undergone focal radiation found a 100% incidence of at least 1 microbleed 2 years following radiation. 21 Belliveau et al 19 further demonstrated the increased ability of 7T to detect radiation-related cerebral microbleeds using SWI, apparent transverse relaxation, and quantitative susceptibility mapping. Bian et al 23 found significantly more cerebral microbleeds in 7/10 patients with gliomas who underwent radiation therapy using 7T SWI compared with 3T SWI.…”
Section: Intracranial Tumorsmentioning
confidence: 99%